Sejarah dunia : untuk SMA - Sutrisno Kutoyo (Wijaya, 1976)
ast jil.1 =c.1-3 jil.2 =c.1-3 jil.3 =c.1/ast jil.3 =c.2/ast jil.1 =c.4/ir,jil.3,c.3/oen, jil.3=c.4/ast jil.3 =c.5/oen, jil1=c.5/nr,jil.3=.15-16